Elucidation of the bonding of a near infrared dye to hollow gold nanospheres – a chalcogen tripod. Issue 8 (27th April 2016) - Kearns, H.; Sengupta, S.; Sasselli, I. Ramos; Bromley III, L.; Faulds, K.; Tuttle, T.; Bedics, M. A.; Detty, M. R.; Velarde, L.; Graham, D.; Smith, W. E.
Abstract : Determining how Raman labels orientate on the surface of HGNs to aid in future advancements of designing NIR nanosensors. Abstract : Infrared surface enhanced Raman scattering (SERS) is an attractive technique for the in situ detection of nanoprobes in biological samples due to the greater depth of penetration and reduced interference compared to SERS in the visible region. A key challenge is to understand the surface layer formed in suspension when a specific label is added to the SERS substrate in aqueous suspension. SERS taken at different wavelengths, theoretical calculations, and surface-selective sum frequency generation vibrational spectroscopy (SFG-VS) were used to define the surface orientation and manner of attachment of a new class of infrared SERS labels with a thiopyrylium core and four pendant 2-selenophenyl rings. Hollow gold nanospheres (HGNs) were used as the enhancing substrate and two distinct types of SERS spectra were obtained. With excitation close to resonance with both the near infrared electronic transition in the label (max 826 nm) and the plasmon resonance maximum (690 nm), surface enhanced resonance Raman scattering (SERRS) was obtained. SERRS indicates that the major axis of the core is near to perpendicular to the surface plane and SFG-VS obtained from a dried gold film gave a similar orientation with the major axis at an angle 64–85° from the surface plane. Longer excitation wavelengths give SERS with little or no molecular resonance contribution and new vibrations appeared with significant displacements between the thiopyrylium core and the pendant selenophene rings. Analysis using calculated spectra with one or two rings rotated indicates that two rings on one end are rotated towards the metal surface to give an arrangement of two selenium and one sulphur atoms directly facing the gold structure. The spectra, together with a space filled model, indicate that the molecule is strongly adsorbed to the surface through the selenium and sulphur atoms in an arrangement which will facilitate layer formation.